Exploring Gender Based Differences in Resilience Among Indonesian University Students Through Rasch Model - Maria Oktasari; Hayu Stevani; Herul Wahyudin; Fijriani Fijriani; Restu Dwi Ariyanto; Leung Hoi-yung (Journal of Counseling and Educational Research, 2025)
Resilience is a crucial psychological construct that enables university students to navigate academic and social challenges effectively. Despite its significance, gender-based differences in resilience remain underexplored in the context of Indonesian higher education. This study aimed to identify differences in resilience between male and female students using a psychometric approach based on the Rasch Model. A total of 1,046 students from public and private universities across 19 provinces in Indonesia participated in the study by completing a 20-item resilience scale tailored to academic settings. The Rasch analysis was used to assess item reliability, unidimensionality, and differential item functioning (DIF) across gender groups. The results indicated strong psychometric performance, with person reliability of 0.89 and item reliability of 0.99. The scale was confirmed to be unidimensional, and item difficulty ranged from −0.99 to 1.33 logits. Although the raw scores of male and female students were similar, DIF analysis revealed a statistically significant difference in resilience levels (F = 8.79, p = 0.003), with male students scoring higher (mean logit = 2.16) than female students (mean logit = 1.86). These findings highlight the presence of gender-based differences in resilience and emphasize the need for culturally sensitive interventions tailored to the psychological needs of each gender in higher education settings. The Rasch Model proved to be a robust method for detecting subtle psychological variations in diverse student populations.